Critical Discourse Analysis on the Causes of South Kalimantan Floods in Tirto.id as Alternative Teaching Materials for Explanatory Texts in High Schools - Sukirno; Suta Wardianto, Bayu (International Proceedings of Nusantara Raya, 2022)
Critical discourse analysis (AWK) becomes an interesting study, because in a discourse is not solely seen from the aspect of what is written or the aspect spoken. AWK Van Dijk model becomes its own characteristic because in it there are many parts such as super structure, macro and micro structure. In the online news that there is a Tirto.id page about the causes of floods in South Kalimantan, there are many news stories that are found the same, but have differences in intent and purpose. The cause of this flood became a debate between parties and circles so it was packed with interest by Tirto.id. This research uses qualitative methods of desriptive by parsing the data using documentation techniques and analytical techniques. This study produced data and analysis that discussed superstructure, macro structure, and microstructure contained in three online news themed on the causes of flooding in South Kalimantan. From the online news can also be used as teaching material in the learning of explanatory texts, to increase knowledge about the news in the text read or heard.